Barriers to accessing eye care services among visually impaired populations in rural Andhra Pradesh, South India - Kovai, Vilas (Medknow Publications, 2007)
PURPOSE: To understand the reasons why people in rural south India with visual impairment arising from various ocular diseases do not seek eye care. MATERIALS AND METHODS: A total of 5,573 persons above the age of 15 were interviewed and examined in the South Indian state of Andhra Pradesh covering the districts of Adilabad, West Godavari and Mahaboobnagar. A pre-tested structured questionnaire on barriers to eye care was administered by trained field investigators. RESULTS: Of the eligible subjects, 1234 (22.1%, N=5573)) presented with distant visual acuity < 20/60 or equivalent visual field loss in the better eye. Of these, 898 (72.7%, N=1234) subjects had not sought treatment despite noticing a decrease in vision citing personal, economic and social reasons. The analysis also showed that the odds of seeking treatment was significantly higher for literates [odds ratio (OR) 1.91, 95% confidence interval (CI) 1.38 to 2.65], for those who would be defined as blind by visual acuity category (OR 1.35, 95% CI 0.96 to 1.90) and for those with cataract and other causes of visual impairment (OR 1.50, 95% CI 1.11 to 2.03). Barriers to seeking treatment among those who had not sought treatment despite noticing a decrease in vision over the past five years were personal in 52% of the respondents, economic in 37% and social in 21%. CONCLUSION: Routine planning for eye care services in rural areas of India must address the barriers to eye care perceived by communities to increase the utilization of services.